2012
DOI: 10.3389/fphar.2012.00068
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrins – An Update

Abstract: Metalloporphyrins are structural analogs of heme and their potential use in the management of neonatal hyperbilirubinemia has been the subject of considerable research for more than three decades. The pharmacological basis for using this class of compounds to control bilirubin levels is the targeted blockade of bilirubin production through the competitive inhibition of heme oxygenase (HO), the rate-limiting enzyme in the bilirubin production pathway. Ongoing research continues in the pursuit of identifying ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 113 publications
2
62
0
Order By: Relevance
“…They appeared to have significant effects in lowering plasma bilirubin levels, however, were not shown to be superior to phototherapy in treating neonatal jaundice. In addition, treated infants showed a photosensitivity when phototherapy was applied (10). In addition, we have found that zinc deuteroporphyrin bis-glycol (ZnBG) and chromium mesoporphyrin (CrMP) have photo-and chemical toxicity, respectively, despite both being highly potent (26).…”
Section: Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…They appeared to have significant effects in lowering plasma bilirubin levels, however, were not shown to be superior to phototherapy in treating neonatal jaundice. In addition, treated infants showed a photosensitivity when phototherapy was applied (10). In addition, we have found that zinc deuteroporphyrin bis-glycol (ZnBG) and chromium mesoporphyrin (CrMP) have photo-and chemical toxicity, respectively, despite both being highly potent (26).…”
Section: Articlesmentioning
confidence: 99%
“…or i.m.) (10). The oral route is the most convenient and comfortable means of administration for pharmaceutical products (29), and for Mps, the "first pass effect" allows for a targeted inhibition of HO activity in the liver, the main organ that degrades excessive heme loads in hemolytic conditions.…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of bilirubin vary with age (Dennery, 2012), and metalloporphyrins have been suggested to reduce excessive hyperbilirubinemia and brain damage in newborns (Schulz et al, 2012).…”
mentioning
confidence: 99%
“…reported that metalloporphyrins interact with many heme-containing enzyme systems, including soluble guanylyl cylase (sGC), nitric oxide synthase (NOS), and cytochrome P450 (CYP450) [247].…”
Section: The Side Effects Of Metalloporphyrinsmentioning
confidence: 99%